Pengembangan Modul Materi Matriks Dengan Pendekatan Realistic Mathematics Education (RME) Untuk Kelas X SMK Muhammadiyah 1 Sukoharjo - Setyanto, Yainuri; , Prof. Dr. Sutama, M.Pd (2017)
The purpose of this research and development is (1) to develop module on matrix material with RME approach for class X students of SMK (2) to describe the quality of module in matrix material with RME approach for students of class X SMK evaluated from aspect of validity and feasibility. This research is a research &development with five stages of development that is Analysis, Planning, Development, Verification, and Validation. In the Analysis phase, the researcher conducts curriculum analysis, teacher response analysis and analysis of student characteristics. At the planning stage, the researcher outlines the contents of the module, collects the reference book, determines the module specifications, and develops the module assessment instrument. At the Development stage, researchers develop modules according to the initial design, assessing the quality of the modules. In the Product verification phase, the module that has been developed is then verified by the material expert (expert lecturer) and the practitioner (subject teacher) through the FGD and then carried out the initial revision. At the Validation stage, an assessment of modules by material experts, practitioners, and students through a questionnaire is used as the basis for the module's feasibility assessment and subsequent revisions. This research produces module of with RME approach. The results showed that: (1) based on the assessment of the quality of the module by the material experts and pratktisi expressed Valid with the average score of 4.14 respectively with the percentage of 83% included in the category valid and 4.42 with the percentage of 88% Category is very good. (2) based on the student response questionnaire, developed modules are considered feasible with an average score of 4.11 with a percentage of 82% included in either category.